SEM Analysis: Internal Control Quality and Decision-Making Quality at Vocational High School - Lestari, Afifah Tripuji; Hamidi, Nurhasan (Proceedings International Conference on Education Innovation and Social Science, 2024)
The study aimed to examine (1) internal quality audit relationship between internal control quality at Vocational High School and (2) internal quality audit relationship between decision-making quality at Vocational High School. The study, which relied on the quantitative approach, targeted 57 of A-accredited public and private Vocational High School in Solo Raya, which includes Surakarta City, Sukoharjo Regency, Karanganyar Regency, Sragen Regency, Klaten Regency, and Boyolali Regency. The questionnaires were adopted as a tool for data collection and the Structural Equation Modelling (SEM) with SmartPLS 3.0 Version software was used to analyses data. The study found that internal quality audit has a positive and significant relationship between internal control quality at Vocational High School. The study also found that internal quality audit has a positive and significant relationship between decision-making quality at Vocational High School.